Sales career tenureship among insurance salesperson - Masilah binti Mohamad (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
One of the major concerns under the organization of human resources is regarding the sales management. This includes the tenure period holds by the salesperson within the organization. Tenure has become one of the main concerns due to the reason that the cost of acquiring and recruiting a new salesperson is high. Moreover, if the turnover rate is high, it would also bring negative impacts toward the organization's competitiveness and productivity. The purpose of this study is to explore the various factors that influence the sales career tenureship among insurance salesperson. For that reason, data were collected from 204 insurance salesperson using self-administered questionnaires throughout Kuala Lumpur and Klang Valley areas. SPSS and AMOS were used for the purpose of data analysis. First, the Exploratory Factor Analysis (EFA) was performed in order to extract the factor underlying for each of the measured variable of interest. Then, Confirmatory Factor Analysis (CFA) was performed based on the new factors extracted from EFA. Based on the result obtained from the CFA, Structural Equation Modelling (SEM) was then drawn to examine the developed hypothesis as well as to test the fitness of the proposed model. Findings revealed that, there is indeed significant positive impact of intrinsic motivation on job satisfaction, organizational commitment, and employee's productivity. Similarly, it was also found that, intrinsic motivation, job satisfaction and organizational commitment have a very significant positive impact on tenure. Besides, job satisfaction also shows significant positive impact on organizational commitment. In sum, the finding of the research can bring some weight towards the managerial implication, especially in the area of human resource management.